Analisis Perbandingan Konsentrasi Air Sulfur Terhadap Pertumbuhan Bibit Bambu Ampel (Bambusa vulgaris) (Studi Kasus Desa Mengeruda Kecamatan So’a, Kabupaten Ngada, Provinsi Nusa Tenggara Timur) - Asri Meyrani Rahelia Banoet; Mamie E. Pellondo'u; Wilhelmina Seran; Norman P. L. B. Riwu Kaho (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2024)
Sulfur or sulfur is one of the essential nutrients that plants need for their growth. Plants that lack the nutrient sulfur will cause symptoms of chlorosis (pale to yellow leaves), slow growth and development so that the plants grow thin and stunted. Excess sulfur elements cause the pH value in plants to be too acidic so that the leaves fall off easily. This research aims to determine the effect of sulfur water concentration on the growth of ampel bamboo seedlings (Bambusa vulgaris) and the concentration of sulfur water that has the best influence on the growth of ampel bamboo seedlings (Bambusa vulgaris). The samples were given different treatments. There were 4 variables observed in this research, namely, Percentage of Living Cuttings, Shoot Length, Number of Leaves and Root Length. The research results showed that the concentration of sulfur water did not have a real influence on the variable percentage of survival of cuttings, but had a very real influence on the variables shoot length, number of leaves and root length. On the shoot length variable, the treatment that gave the best effect was the treatment with a sulfur concentration of 300 ppm, on the leaf number variable, the treatment that gave the best effect was the treatment with a concentration of 300 ppm, and on the root length variable, the treatment that gave the best effect was the treatment with a concentration of 300 ppm.